OGC P01 Cost utility analysis of a prehabilitation programme in patients undergoing treatment for oesophageal cancer. (7th December 2022) - Powell, Arfon; Allen, Sophie; Casey, Patrick; Hunt, Julie; Prabhu, Pradeep; Jack, Sandy; Rockall, Timothy; Preston, Shaun; Sultan, Javed
Abstract: Background: Treatment of oesophageal cancer is associated with significant morbidity which has an impact on longer term survival. Prehabilitation has been shown to reduce post-operative morbidity and mortality. The aim of this study was to undertake a cost-utility analysis to determine if, based on quality adjusted life-years, prehabilitation should be universally implemented in patients undergoing treatment for oesophageal cancer. Methods: Patients with oesophageal cancer who were recruited to a randomised control trial were retrospectively analysed. Three-years follow-up was available for calculating overall survival. Costs were calculated based on network, staging, and treatment algorithms. QALYs were calculated as a matrix cost of treatment, quality of life, and overall survival. Overall survival was calculated from time of diagnosis to death or censorship at three-years follow up. Results: Thirty-nine patients were randomised to prehabilitation (n=20, 51%) or standard care (n=19, 49%). The median cost per patient for treatment was £46, 770.16 (Inter quartile range (IQR) 41, 907.21–58, 984.21). The overall cost per patient in the prehabilitation group was lower, £44, 382.99 (IQR 42, 022.86–54, 068.23), when compared with standard care per patient £51, 538.07 (IQR41, 907.21–68, 734.33). The mean survival was 24.7 months in the prehab group compared with 27.7 months in the control group (p=0.523). The cost per-QALY for the prehabilitation group was £24, 899.06 compared with £25, 781.71 in the standard care group. Conclusions: In the setting of a randomised control trial, prehabilitation is clinically effective with observed reductions in total treatment costs and a cheaper cost per QALY.